The Obstructions of Word Pronunciation in Studying English for Seventh Grade Students - Khoirul Umam (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
Recently the students have many obstructions on the words pronunciation style in studying English speech. So, the purpose of this research is to know the students English ability whether they can face the obstructions of words pronunciation in their English speech. This research used a descriptive qualitative design to obtain data concerning the research problems. There are three kinds of instrument used by the researcher to collect the data. They are questionnaire, interview, and practice to pronounce of word by reading. From the questionnaire, it was found 81 percent of students have the obstruction of words pronunciation style in learning English speech. From the interview found that there are 19 students can give some objective answers to the researcher and there are 6 students cannot give the unreasonable answer, meaning that allmost all students have problems in pronuncing the word. From practicing to pronounce words by reading can be seen from the test that there are several students who got obstruction in word pronunciation style in English study. From that, the students are expected to pay more attention to teachers explanation at the classroom to have certain ways to enhance vocabulary skills and by reading English texts.Akhir-akhir ini siswa memiliki banyak kendala pada gaya pengucapan kata-kata dalam mempelajari pidato bahasa Inggris. Jadi, tujuan dari penelitian ini adalah untuk mengetahui kemampuan bahasa Inggris siswa apakah mereka dapat menghadapi hambatan pengucapan kata dalam pidato bahasa Inggris mereka. Penelitian ini menggunakan desain deskriptif kualitatif untuk memperoleh data mengenai permasalahan penelitian. Ada tiga macam instrumen yang digunakan peneliti untuk mengumpulkan data. Yaitu angket, wawancara, dan latihan melafalkan kata dengan membaca. Dari angket, ditemukan 81 persen siswa mengalami hambatan gaya pengucapan kata dalam pembelajaran pidato bahasa Inggris. Dari hasil wawancara ditemukan bahwa ada 19 siswa yang dapat memberikan jawaban yang objektif kepada peneliti dan ada 6 siswa yang tidak dapat memberikan jawaban yang tidak masuk akal, artinya hampir semua siswa mengalami kesulitan dalam pengucapan kata. Dari latihan melafalkan kata dengan membaca dapat dilihat dari tes bahwa ada beberapa siswa yang mengalami hambatan dalam gaya pengucapan kata dalam pembelajaran bahasa Inggris. Dari situ, siswa diharapkan lebih memperhatikan penjelasan guru di kelas untuk memiliki cara-cara tertentu untuk meningkatkan kemampuan kosakata dan dengan membaca teks bahasa Inggris.